Sistem Rekomendasi Lokasi Lapangan Futsal Berbasis Android Dengan GDSS dan LBS - Jermias Kristian; Ratih Kartika Dewi; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Futsal is a fitness sport that is carried out by two groups, each group consisting of five players, including one goalkeeper. Due to futsal sports that cannot be done alone, a common problem that is often encountered when you want to play futsal is the selection of the field where there are often differences in opinion between each player based on the tastes or preferences of the participating players. Differences in futsal field preferences for players can be obtained based on differences in price and distance, as an example. The purpose of this futsal field recommendation system is to combine the preferences of the players into one group recommendation, utilizing the TOPSIS and Borda decision support systems, the author succeeded in creating the application. The futsal field recommendation application is built on the Android operating system on the grounds that the use of Android alone reaches more than 90% in Indonesia, and 70% worldwide. The application is also built with LBS by utilizing GPS sensors so that the application is able to calculate the route between the user's current position and the position of the field that you want to go to. The results of this study were tested using algorithm validation testing to match the application output value with manual calculations, then blackbox testing which also gave 100% valid results for each test and also the SUS (System Usability Scale) survey where the author got 84.8% or B results for SUS testing.